“Vanishing Penis” and Urinary Retention due to Locally Destructive Penile Cancer - Petros Sountoulides; Athanasios Bantis; Ioannis Zachos; Irene Asouhidou; Athanasios Pantazakos (The Scientific World Journal)
Penile carcinomas are relatively rare. They usually arise from precancerous lesions and present in the form of ulcerative or exophytic tumors. They rarely give rise to urinary symptoms and complications, and are usually easy to diagnose. We present a case of an 82-year-old man with chronic urinary retention due to urethral dissemination by a locally destructive penile lesion. The penis was literally “vanished” by the lesion down to the level of the pubic bone without, interestingly, having spread to the local lymph nodes or given rise to distant metastases. A temporary suprapubic catheter was placed, followed by a perineal urethrostomy in order to reverse the established renal failure.